Association of heterogeneous MYCN amplification with clinical features, biological characteristics and outcomes in neuroblastoma: A report from the Children's Oncology Group. (July 2020) - Campbell, Kevin; Naranjo, Arlene; Hibbitts, Emily; Gastier-Foster, Julie M.; Bagatell, Rochelle; Irwin, Meredith S.; Shimada, Hiroyuki; Hogarty, Michael; Park, Julie R.; DuBois, Steven G.
Abstract: Purpose: MYCN amplification (MNA) is associated with poor outcomes in neuroblastoma. Less is known about heterogeneous MNA within a tumour. We compared clinical characteristics, biologic features and clinical outcomes of patients with heterogeneous MNA to patients with either homogeneous MNA or MYCN wild-type tumours. Patients and methods: In this retrospective cohort study, we categorized patients as having tumours with MYCN wild-type, homogeneous MNA (>20% amplified tumour cells) or heterogeneous MNA (≤20% amplified tumour cells). We used chi-squared or Fisher's exact tests to compare features between groups. We used log-rank tests and Cox models to compare event-free survival (EFS) and overall survival (OS) between groups. Results: MYCN status and heterogeneity status (if amplified) could be ascertained in diagnostic tumour samples from 5975 patients, including 57 (1%) with heterogeneous MNA, 981 (16.4%) with homogeneous MNA, and 4937 (82.6%) with MYCN wild-type tumours. Multiple clinical and biological features differed between patients with heterogeneous vs. homogeneous MNA, including enrichment for thoracic primary sites and paucity of 1p loss of heterozygosity with heterogeneous MNA (p < 0.0001). Importantly, EFS and OS were not significantly different between patients with heterogeneous vs. homogeneous MNA. Further, EFS and OS for patients with heterogeneous MNA were significantly inferior to patients with wild-type MYCN . Conclusion: Although neuroblastomas with heterogeneous MNA demonstrate significantly different biological and clinical patterns compared with homogeneous MNA, prognosis is similar between the two groups. These results support current practice that treats patients with heterogeneous MNA similarly to patients with homogeneous MNA. Highlights: MYCN amplification (MNA) is a known adverse prognostic factor in neuroblastoma. Only 1% of neuroblastomas have heterogeneous MNA, with MNA in ≤20% of tumour cells. Clinical and biological features are distinct for heterogeneous MNA. Outcomes with heterogenous MNA are worse than with wild-type MYCN .